App-Based Volleyball Scoreboard Performance Evaluation - Sholeh Agus Santoso; M. Haris Satria (Indonesian Journal of Physical Education and Sport Science)
Study purpose. This research aims to develop and evaluate an application-based volleyball scoreboard game device designed to facilitate the process of recording and managing scores in real time.